Mirror Neurons in a New World Monkey, Common Marmoset - Suzuki, Wataru; Banno, Taku; Miyakawa, Naohisa; Abe, Hiroshi; Goda, Naokazu; Ichinohe, Noritaka (Frontiers in Neuroscience, 2015)
Mirror neurons respond when executing a motor act and when observing others’ similar act. So far, mirror neurons have been found only in macaques, humans and songbirds. To investigate the degree of phylogenetic specialization of mirror neurons during the course of their evolution, we determined whether mirror neurons with similar properties to macaques occur in a New World monkey, the common marmoset (Callithrix jacchus). The ventral premotor cortex (PMv), where mirror neurons have been reported in macaques, is difficult to identify in marmosets, since no sulcal landmarks exist in the frontal cortex. We addressed this problem using “in vivo” connection imaging methods. That is, we first identified cells responsive to others’ grasping action in a clear landmark, the superior temporal sulcus (STS), under anesthesia, and injected fluorescent tracers into the region. By fluorescence stereomicroscopy, we identified clusters of labelled cells in the ventrolateral frontal cortex, which were confirmed to be within the ventrolateral frontal cortex including PMv after sacrifice. We next implanted electrodes into the ventrolateral frontal cortex and STS and recorded single/multi-units under an awake condition. As a result, we found neurons in the ventrolateral frontal cortex with characteristic “mirror” properties quite similar to those in macaques. This finding suggests that mirror neurons occur in a common ancestor of New and Old World monkeys and its common properties are preserved during the course of primate evolution.